Rôle du pharmacien d’officine dans la prise en charge des maladies coronariennes - MERIKHI , Rami; NOUI , Zakaria; SAADI , Mohamed; BOUHEDADJA , Zahia (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Déppartement de Pharmacie, 2025)
Coronary artery disease, the most common form of heart disease, results from the gradual narrowing of the arteries that supply blood to the heart, caused by the buildup of atherosclerotic plaques. It is a widespread chronic condition, yet its progression can be controlled by managing risk factors, both in primary and secondary prevention. Drug therapies, combined with lifestyle and dietary measures, are essential to limit complications. Therefore, it is crucial for patients to understand and adhere to these measures. The community pharmacist, as a highly accessible healthcare professional, plays a central role in this regard. This work is based on two complementary field surveys: one conducted among coronary patients, and the other among community pharmacists. Its goal is to gain a deeper understanding of current support practices, patient expectations, and field-based limitations. The findings reveal that, despite a basic awareness of their treatment, many patients still lack knowledge about drug interactions and warning signs. As a medication expert, the pharmacist is perfectly positioned to fill these gaps by informing, guiding, reassuring, and preventing medication errors. However, the pharmacist’s role in therapeutic education remains underutilized and insufficiently recognized. With the growing burden of chronic diseases, this role is bound to become increasingly vital. In conclusion, this study highlights the need for a more active and structured involvement of pharmacists in the care of coronary patients. By asserting their full expertise, pharmacists can greatly contribute to improving patients’ quality of life and reducing complication
تمثل أمراض الشرايين التاجية الشكل الأكثر شيو ًعا من أمراض القلب، وهي ناتجة عن تضيق تدريجي في الشرايين التي تزود القلب بالدم، بسبب تراكم لويحات دهنية (تصلب الشرايين). وتُعد من الأمراض المزمنة المنتشرة، ويمكن السيطرة على تطورها من خلال التحكم الدقيق بعوامل الخطر، سواء في إطار الوقاية الأولية أو الثانوية. تُعد العلاجات الدوائية، إلى جانب الإجراءات الصحية والغذائية، ضرورية لتقليل المضاعفات. ومن الضروري أن يفهمها المريض جيدًا ويطبقها بدقة. وهنا يلعب الصيدلي، باعتباره مقدم رعاية صحية متا ًحا وسهل الوصول، دو ًرا محوريًا في هذا المجال. يعتمد هذا العمل على دراستين ميدانيّتين متكاملتين: الأولى موجهة للمرضى المصابين، والثانية موجهة للصيادلة العاملين في الصيدليات. ويهدف إلى فهم أفضل للممارسات الحالية في مرافقة المرضى، وتحديد احتياجاتهم، والوقوف على أوجه القصور الميدانية. تكشف النتائج أن العديد من المرضى، رغم معرفتهم الجزئية بالعلاج، لا يزالون يجهلون جوانب هامة كالتداخلات الدوائية أو علامات الإنذار. وبصفته المختص الأول في علم الأدوية، فإن الصيدلي مؤهل تما ًما للاستجابة لهذه الثغرات، من خلال تقديم المعلومات، والتوجيه، والطمأنة، والوقاية من الأخطاء. ورغم ذلك، يبقى دوره في التثقيف العلاجي غير مستغل بالشكل الكافي وغير معترف به رسميًا، في وقت تتزايد فيه أعباء الأمراض المزمنة. لذا أصبح من الضروري تعزيز مكانته ضمن منظومة الرعاية. وباختصار، تبرز هذه الدراسة أهمية إشراك الصيدلي بشكل أنشط وأكثر تنظي ًما في رعاية مرضى الشرايين التاجية، وتمكينه من أداء دوره العلمي والمهني الكامل بما يساهم في تحسين جودة حياة المريض وتقليل المضاعفات